Cost-effectiveness of Collaborative Care for Depression in Human Immunodeficiency Virus Clinics - Painter, Jacob T (J Acquir Immune Defic Syndr, 2015)
OBJECTIVE: To examine the cost-effectiveness of the HITIDES intervention. DESIGN: Randomized controlled effectiveness and implementation trial comparing depression collaborative care with enhanced usual care. SETTING: Three Veterans Health Administration (VHA) HIV clinics in the Southern US. SUBJECTS: 249 HIV-infected patients completed the baseline interview; 123 were randomized to the intervention and 126 to usual care. INTERVENTION: HITIDES consisted of an off-site HIV depression care team that delivered up to 12 months of collaborative care. The intervention used a stepped-care model for depression treatment and specific recommendations were based on the Texas Medication Algorithm Project and the VA/Department of Defense Depression Treatment Guidelines. MAIN OUTCOME MEASURE(S): Quality-adjusted life years (QALYs) were calculated using the 12-Item Short Form Health Survey, the Quality of Well Being Scale, and by converting depression-free days to QALYs. The base case analysis used outpatient, pharmacy, patient, and intervention costs. Cost-effectiveness was calculated using incremental cost effectiveness ratios (ICERs) and net health benefit (NHB). ICER distributions were generated using nonparametric bootstrap with replacement sampling. RESULTS: The HITIDES intervention was more effective and cost-saving compared to usual care in 78% of bootstrapped samples. The intervention NHB was positive and therefore deemed cost-effective using an ICER threshold of $50,000/QALY. CONCLUSIONS: In HIV clinic settings this intervention was more effective and cost-saving compared to usual care. Implementation of off-site depression collaborative care programs in specialty care settings may be a strategy that not only improves outcomes for patients, but also maximizes the efficient use of limited healthcare resources.